The role of leadership in digital transformation – a paradox way to improve operational performance - Dióssy, Kitti; Losonci, Dávid; Aranyossy, Márta; Demeter, Krisztina (Journal of manufacturing technology management, 2025)
PurposeLeadership has been identified as a crucial driver of efficient deployment of any Operations Management (OM) paradigm. Our work focuses on digitalisation, a recent OM paradigm, and analyses the mediating effect of digital transformation (DT) on the relationship between task-oriented and relationship-oriented leadership styles (LSs) and operational performance (OP) improvements in the manufacturing context.Design/methodology/approachThe authors employed survey data from Hungarian manufacturing firms. Hypotheses are tested using structural equation modelling.FindingsTask-oriented and relationship-oriented LSs exert distinct influences on DT and OP improvements. The results indicated that task-oriented LS drives OP improvements through its impact on DT. The relationship-oriented LS does not influence DT. Regarding the implications for OP improvements, we revealed a leadership paradox as the indirect positive impact of task-oriented LS may be offset by the direct negative influence of relationship-oriented LS.Research limitations/implicationsThe results are most pertinent to manufacturing firms that have already started their digital journey. Further studies must clarify how managers’ cultural embeddedness (i.e. general perceptions about efficient leadership in their country or region, national culture) could influence findings. Finally, to learn about the effective long-term behaviours of leaders might require different empirical methods.Originality/valueTo the best of the authors’ knowledge, this study represents one of the first survey-based examinations of CEOs on the ways how LSs drive the effective deployment of DT in manufacturing firms. Our findings demonstrate a leadership paradox at the nascent stages of DT in manufacturing firms.